Automatic Grain Dryer Using Solar Power Plant Backup - Hendrian, Yuyasmie Yastha; Machdi, Agustini Rodiah; Notosudjono, Didik (Journal of Energy and Electrical Engineering, 2025)
Grain drying is a critical step in rice post-harvest handling to lower moisture to safe levels for storage and milling. This study designs and develops an automatic, sensor-based grain dryer powered by the grid with a solar PV (PLTS) backup. The goal is efficient, stable drying that satisfies SNI 1628:2015 premium quality (no more than 14% moisture). The system monitors and controls temperature and humidity, while DC motors and blowers accelerate drying to improve uniformity and product quality. Solar energy provides resilient backup during grid outages, supports continuous operation, and helps reduce dependence on conventional electricity. Prototype tests show a peak PV output of 17.08 W at 12.24% panel efficiency. Operating the dryer for 6 hours requires ~126.24 Wh. Accordingly, a battery of about 1,130 mAh capacity is estimated, with a full-charge duration of ~7.65 hours. To supply 126.24 Wh with one day of autonomy, a PV module of approximately 0.009618 kWp (10 Wp) is recommended.